Diversity of Rhizosphere Fungi Originating from Cocoa and Mahogany Plants in Tanuntung Village - Bau Mirta; Muh. Noor Amin Sholeh; Muhlizha Azhari Nur; Mita Yusri (Jurnal Biologi Tropis, 2026)
Cocoa and mahogany are plantation crops that are often intercropped on the same agricultural land and are widely cultivated in Bulukumba, South Sulawesi including in the village of Tanuntung, Hero Lange-lange Subdistrict because they hold promising economic value; in the field of soil science, they can even be used to assess fungal diversity  in the root zone as an indicator of soil fertility. In the fields of soil science and agricultural science, fungi are organisms that act as decomposers and biological agents and are capable of forming mutualistic symbiotic relationships with certain plant organs, such as roots. Therefore, this study aims to observe and calculate the diversity of rhizosphere fungi from cocoa and mahogany plants in Tanuntung Village with the hope of providing an important picture of the complexity of the microbial ecosystem around the root area and its correlation to soil fertility. The research method used was exploratory descriptive research, which involved collecting soil samples in the village of Tanuntung, followed by fungal isolation, fungal identification, screening of isolates, and analysis of rhizosphere fungal diversity. The results of the study showed that the calculation of the IKC value in the cocoa and mahogany rhizosphere was included in the high criteria with the IKC value obtained being 1.24 (cocoa) and 1.20 (mahogany). And based on the results of the identification carried out, the cocoa and mahogany rhizospheres have a diversity of fungi from the same species, namely from the genus Aspergillus sp., Fusarium sp., Penicillium sp. and Rhizopus sp. but the total number of fungi is different. With the high diversity of rhizosphere fungi, it proves that there is a good mutualistic symbiosis in the soil around the root area with fungi, which can also be used as a reference to determine good soil biological quality.